Stories Re-Told: Synthesizing the Vocabulary of Adaptation - Borynec, Anna (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2020)
This paper introduces three umbrella terms (Literal Adaptation, Spirit Adaptation, and Creative Adaptation) that define the broad approaches to creating an adaptation through the consideration of the literature of six different fields and their approaches to the study of adaptation. They are as follows: the study of Classical Mythology (a sub-set of Classics), Cultural Studies, Adaptation Theory (from Film Studies), Fan Fiction Studies (from Fan Studies), Folklore Studies, and Translation Studies. While Library and Information Studies (LIS) does occasionally deal with adaptation, often in the form of Children's Literature and/or Fairy Tales, there is no widely-accepted theory or method to doing so. Therefore it is absent from the six disciplines that were reviewed, though it has substantial cross-over with each. As scholarship becomes more interdisciplinary, juggling the terms of a variety of fields becomes more important and more challenging. This paper aims to provide three accessible terms for those interested in studying adaptions from a broad or cross-disciplinary perspective that can substitute for the lengthy and specialized vocabulary of each individual discipline. It may also provide an example for others looking to similarly synthesize a set of cross-disciplinary vocabularies.